Association between obstructive sleep apnea and multiple adverse clinical outcomes: evidence from an umbrella review - Wang, Qian; Zeng, Hong; Dai, Jindong; Zhang, Ming; Shen, Pengfei (Frontiers in Medicine, 2025)
Background and objectiveIn recent years, there has been a notable rise in awareness regarding obstructive sleep apnea (OSA), and a significant number of potential OSA cases have been identified. Numerous studies have established associations between OSA and various adverse clinical outcomes. This umbrella review aims to summarize and evaluate the available evidence on the relationship between OSA and multiple adverse clinical outcomes.MethodsPubMed, Embase, and Web of Science databases were systematically searched from inception to September 2023. The AMSTAR and GRADE were used to evaluate the quality of meta-analysis literature and classify the quality of literature evidence. Furthermore, the size of the effect size of the association between OSA and adverse clinical outcomes were assessed by using either a random or fixed-effect model and 95% confidence interval (CI).ResultsA total of 27 meta-analyses were enrolled with 43 adverse clinical outcomes. The umbrella review primarily reported the associations between sleep apnea syndrome and thyroid cancer (HR = 2.32,95%CI:1.35–3.98), kidney cancer (RR = 1.81, 95% CI: 1.20–2.74), liver cancer (RR = 1.19, 95% CI: 1.10–1.29), GERD (Gastroesophageal reflux disease)(OR = 1.53, 95% CI: 1.23–1.91), Atrial fibrillation (AF) (OR = 2.54, 95% CI: 2.20–2.92), osteoporosis (OR = 2.03, 95% CI: 1.26–3.27), and diabetes (OR = 1.40, 95% CI: 1.32–1.48). Overall, the AMSTAR rating scale and GRADE quality assessment included in the meta-analysis were generally low.ConclusionOur study shows that OSA is significantly associated with a variety of adverse clinical outcomes, especially an increased risk of certain malignancies, and some adverse clinical outcomes are closely related to OSA severity.